Pioneering price level targeting: The Swedish experience 1931-37 - Claes Berg; Lars Jonung (Sveriges Riksbank, 1998)
In September 1931, Sweden became the first country to make the stabilization of the domestic price level the official goal of its monetary policy, actually the only country that so far has adopted such an explicit price level target. Starting from the issues and concepts familiar from research and policy experience in the 1990s of inflation targeting - as contrasted to price level targeting - this paper examines the evolution of the Swedish price level targeting in the 1930s. We bring out a number of similarities and differences between price stabilization in the 1930s and in the 1990s.
Keywords: 330